GAMBARAN KEMAMPUAN DAN KEMANDIRIAN PERSONAL HYGIENE ANAK USIA SEKOLAH - Mukendah, Rukit Altan Pinari (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Personal hygiene is one of important aspects to support personal health, especially for children, therefore it is important to emphasize indepence of personal hygiene to help children develop self-reliance, If this is not done, children are more likely to suffer from health problems that can lead to psychological problems, this research aims to describe the ability and independency of school aged children in performing personal hygiene Methods: This research is a quantitative study with a simple descriptive research design. The sampling technique in this study is proportionate stratified random sampling, the samples are 103 respondents with unvariate analysis Results: Characteristics of the majority of respondents that have 8-9 year old children are 60 people (58,3%), female are 54 people (52,4%), the majority of respondents which role as mothers are 59 people (57,3%), most of the parents are workers 78 people (75,7%) with the age of 26-35 year old are 55 people (53,4%). The result is the majority of school-aged children which can perform personal hygiene practices are around 54 people (52,4%), and the majority of less independent ones are 73 people (70,9%). Conclusion: The ability of school-aged children is good in practicing personal hygiene but not fully independent to do it. Researchers recommend parents to be more concerned and seek more information and make habituation to children so that children begin to be responsible for themselves to form good habits in children to performing personal hygiene practices so that children have the ability and independence of personal hygiene in order to minimize the development of disorders in children.